The Effect of Kahoot Application on the Students’ Achievement in Reading Comprehension - Nur Fadillah Hasanah; Yunita Mutiara Harahap; Linda Astuti Rangkuti (Journal of English Language and Education, 2023)
The goal of this study is to determine how using Kahoot affected students' reading comprehension proficiency in the second grade throughout the academic year 2022–2023 at Mas Proyek Univa. This study used an experimental research design as its methodology. This study was carried out at Mas Proyek Univa during the XIIth grade. There were three XII grade classes. In each class, there were 30 students. Therefore, there were 90 pupils in all. The sample was taken using a cluster random sampling and lottery technique. The experimental group, designated as XII ipa, and the control group, designated as XII ips, were chosen. 60 students were selected as the sample. A multiple-choice test was the tool utilised to obtain the data. The t-test was used to analyse the data. Following data analysis, it was discovered that tobserved exceeded ttable (13.24 2.00) with a degree of freedom of 58 and a significance level of 0.05. It meant that although ho was turned down, ha was accepted. For the academic year 2022–2023 at Mas Proyek Univa Medan, there is a strong impact of the Kahoot application on students' achievement in reading comprehension